Effect of nerve block combined with superficial general anaesthesia on anaesthetic dosage and anaesthetic awakening in paediatric surgery - Fu Yao; Gang Zhang; Bo Yang; Jilin Xiang (BMC Anesthesiology, 2025)
Abstract Background To compare the effects of nerve block composite general anesthesia and general anesthesia on the dosage of anesthetics and anesthesia awakening in pediatric orthopedic injury patients under anesthesia depth monitoring. Methods Forty pediatric patients with external humerus condylar fractures were randomly distributed into general anesthesia (GA) and nerve block combined with general anesthesia (GNA) groups. Patients in the GA group had induction of anesthesia with propofol at 2.5 mg/kg and remifentanil at 0.6 ug/kg. The Angel-6000D EEG anesthesia depth multi-parameter monitor maintained the EEG awareness index (IOC1) between 40 and 60 and the injury sensitivity index (IOC2) between 30 and 50. Results Both intraoperative propofol maintenance in the GA group (6.74 ± 0.93) and propofol maintenance in the GNA group (5.16 ± 0.76) were significantly different upon comparison between the groups (p < 0.05). Intraoperative remifentanil maintenance differed significantly (p < 0.05) between the GA group (0.26 ± 0.04) and the GNA group (0.10 ± 0.04). Comparison of awakening time: the time of eyelid opening, time of completion order, extubation time, and time of recovery of positioning function in the GNA group were markedly shorter than that of the GA group (p < 0.01) with a high level of significance. Conclusion Nerve block composite general anesthesia under multi-parameter monitoring of depth of anesthesia by Angel-6000D electroencephalogram can lead to a significant reduction in the dosage of propofol and remifentanil, advancement of awakening and extubation time and an increase in the safety of anesthesia in pediatric surgery patients.